2008
DOI: 10.1889/jsid16.12.1203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of display properties on perceived color‐gamut volume and preference

Abstract: Abstract— The effect of varying the color gamut of an extended‐gamut LCD on color appearance and preference was measured psychometrically in two experiments at each of two separate laboratories over a representative set of 10 images each. The first experiment measured the effect of color gamut on appearance, and the effect on the appearance attribute colorfulness was shown to be relatively strong compared with other attributes as the volume of display color gamut is varied. Overall, colorfulness monotonically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…709 standard were preferred, though not to the full extent of the wider gamut boundary. This observation was later confirmed in an experiment, determining the preferred chroma for a larger set of more complex natural images [7]. The image content used in [6] was too limited, but had the advantage that the images were simple, so that it was clear what part of the image was used by the participants to make a judgment.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…709 standard were preferred, though not to the full extent of the wider gamut boundary. This observation was later confirmed in an experiment, determining the preferred chroma for a larger set of more complex natural images [7]. The image content used in [6] was too limited, but had the advantage that the images were simple, so that it was clear what part of the image was used by the participants to make a judgment.…”
Section: Introductionmentioning
confidence: 80%
“…The image content used in [6] was too limited, but had the advantage that the images were simple, so that it was clear what part of the image was used by the participants to make a judgment. More images were used in [4] and [7], but they all were more complex (usually containing more than one color or object), making it unclear what part of the image was used by the participants to tune the preferred chroma. To avoid the latter issue we designed an additional experiment with more images based on one single hue.…”
Section: Introductionmentioning
confidence: 99%
“…As for the Arousal evaluation, our results are similar to those of Ayama et al That study used a conventional LCD and found that that psychophysical evaluations, such as vividness and lightness, increased or decreased monotonously with image chroma. In addition, Sakurai et al used a wide gamut LCD and demonstrated that subjects' sensitivity to colorfulness increased with increasing color gamut volume in which the images were rendered. As the Arousal dimension in our study is related to the evaluation of dull‐vivid , the dimension may reflect the subjective perceptual evaluation toward chroma‐varied images.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on wide color gamut displays have mainly focused on the preferred chroma of natural images . For example, Murdoch et al investigated preferred levels of chroma using an RGB wide gamut display.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation